STUDY OF THE STRENGHT OF THE INFERIOR MEMBRES AFTER A TWELWE WEEKS TRAINING IN ELDERS (Fiep Bulletin - online, 2014)
Introduction: With the population increase of people with age superior to 60 years, the researchers have turned their attentions to questions of the functional capacity and physical dependency. Objective: The present study aimed at verifying the strength of the inferior members in elder people up to 60 years, after 12 weeks of practices of physical activities realized in classes. Methodology: The sample was built upon 13 individuals of both sex, with middle age of 65,69 (s.d.= 4,42) years, participants of a specific program to people of third age. To measure the strength it was used the Sitting and Getting Up Test made by (Matsudo, 2000). The participants, went to the classes three times per week, doing the muscle exercises (one time per week) including extensor chair, flexor chair, aductor, abductor and leg press 45º. During the first 8 weeks the participants realized 2 series of 12 repetitions in each machine and in the other weeks 2 series of 8 repetitions but with increase in the charge. In the other days it was varied the activities with the addition of hikes three times per week. To the analysis of the data was used a descriptive statistics (average and standard deviation) and a “t” test to verify the significant difference between the pre and after-test of the variable. Results: It was observed in the results that the average of the “Sitting and Getting Up” pre-test is of 8,53 and of the after-test is 11,38. The sample in the pre-test cannot be considerate, because its levels are insufficient, but,in the after-test it increases to good leves (Rauchbach,2003). It had a significant difference between the pre and after-test, p=0,000. Conclusions: It may be concluded that after 12 weeks of training and of the realized activities in classes, the individuals had a significant improvement of the strength levels of the inferior members.
Keywords: Strenght; training; elders